0.55x+.05(20-x)=.10(-30)

Simple and best practice solution for 0.55x+.05(20-x)=.10(-30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.55x+.05(20-x)=.10(-30) equation:


Simplifying
0.55x + 0.05(20 + -1x) = 0.10(-30)
0.55x + (20 * 0.05 + -1x * 0.05) = 0.10(-30)
0.55x + (1 + -0.05x) = 0.10(-30)

Reorder the terms:
1 + 0.55x + -0.05x = 0.10(-30)

Combine like terms: 0.55x + -0.05x = 0.5x
1 + 0.5x = 0.10(-30)

Multiply 0.10 * -30
1 + 0.5x = -3

Solving
1 + 0.5x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 0.5x = -3 + -1

Combine like terms: 1 + -1 = 0
0 + 0.5x = -3 + -1
0.5x = -3 + -1

Combine like terms: -3 + -1 = -4
0.5x = -4

Divide each side by '0.5'.
x = -8

Simplifying
x = -8

See similar equations:

| 3x+4x-5+2x-3=180 | | -20x^2-6x=0 | | 4y^2-9y+5=0 | | 49=7(x+2) | | .24y-1.1=.14y+1-.6y | | (3-6x)-4=12 | | -240=12x | | 10n+8=450 | | X^2+8xy-36y^2= | | 9x-27=-41+7x | | -2x-3=4x-15 | | (x^4-1)(x^4-1)(x^4-1)= | | 83.36+5.50x=15.92x | | 7(n-5)=14 | | 9(n+2)=3(n-2) | | 8t=5t | | 5x+13=2(x-12) | | 18=3(n+2) | | (4+x)=-8 | | 6x=5+5 | | 8(n-3)=0 | | 83.36+5.50p=13.92 | | 5b-(2b+8)=16 | | 7(1-a)=-7 | | 866=59r*4 | | 10+x=-x | | 7-2a=21 | | 165t+76=14 | | 12x^2=10x+8 | | 5(a-2)=10 | | 5y-10+y+36=8y+30-6y | | 40=5(3d+2) |

Equations solver categories